Approaches to the study of tourist service (on the case of the Ural mountains) - Zyrianov Aleksandr I.; Zyrianova Inna S.; Myshliavtseva Svetlana E.; Shchepetkova Irina O. (Glasnik Srpskog Geografskog Društva, 2023)
Mountain have long been areas of tourist interest. In connection with the rapid development of the service, the range of tourist activities in the mountains is increasing. The study area is mountainous part of the Ural economic region, the most economically developed part of the Ural Mountains. The paper attempts to structure the tourist service by types of tourism - medical and recreational, skiing, nature-based, industrial, event. As a result, it was revealed that a number of types of tourism form their own service system and are clearly localized in space (health, ski, nature-based tourism), other types of tourism (industrial, event) are not so strictly determined. Medical tourism is the most inert type of tourism. The geography has not undergone significant changes over a long period of time due to the complete dependence on the infrastructure base of the sanatorium-resort complex. Ski tourism is a dynamically developing type of tourism in the region under consideration. Despite the need for significant investment, the network of ski resorts is growing and the range of their tourist services is expanding. Nature-based tourism, natural recreation is the most common type of tourism due to the widespread creation of tourist service facilities with the widest range - recreation centers and tourist bases, guest houses, glamping, campsites, etc. These objects gravitate towards natural attractions, picturesque outskirts of populated areas, points and banks of reservoirs, sustainable tourist routes.